Enhanced l-Malic Acid Production by Aspergillus oryzae DSM 1863 Using Repeated-Batch Cultivation - Schmitt, Vanessa; Derenbach, Laura; Ochsenreither, Katrin (Frontiers in Bioengineering and Biotechnology, 2022)
L-Malic acid is a C4-dicarboxylic acid and a potential key building block for a bio-based economy. Currently, malic acid is synthesized petrochemically and its major market is the food and beverages industry. In future, malic acid might also serve as building block for biopolymers or even replace the commodity chemical maleic anhydride. For a sustainable production of L-malic acid from renewable resources, the microbial synthesis by the mold Aspergillus oryzae is one possible route. As CO2 fixation is involved in the biosynthesis, high yields are possible and at the same time greenhouse gases can be reduced. In order to enhance the production potential of the wild-type strain Aspergillus oryzae DSM 1863, process characteristics were studied in shake flasks, comparing batch, fed-batch and repeated-batch cultivations. In the batch process, a prolonged cultivation time led to malic acid consumption. Keeping carbon source concentration on a high level by pulsed feeding could prolong cell viability and cultivation time, but did not result in significant higher product levels. In contrast, continuous malic acid production could be achieved over 6 exchange cycles and a total fermentation time of 19 days in repeated batch cultivations. Up to 178 g/L L-malic acid were produced. The maximum productivity (0.90 ± 0.05 g/L/h) achieved in the repeated batch cultivation had more than doubled compared to the batch process and also the average productivity (0.42 ± 0.03 g/L/h for 5 exchange cycles and 16 days) was increased considerably. Further repeated batch experiments confirmed a positive effect of regular calcium carbonate additions on pH stability and malic acid synthesis. Besides calcium carbonate, nitrogen supplementation proved to be essential for the prolonged malic acid production in repeated batch. As a prolonged malic acid production was only observed in cultivations with product removal, product inhibition seems to be the major limiting factor for malic acid production by the wild-type strain. This study provides a systematic comparison of different process strategies under consideration of major influencing factors and thereby delivers important insights in natural L-malic acid production.